2005
DOI: 10.1002/hbm.20188
|View full text |Cite
|
Sign up to set email alerts
|

Reading embossed capital letters: An fMRI study in blind and sighted individuals

Abstract: Reading Braille activates visual cortex in blind people [Burton et al., J Neurophysiol 2002;87:589-611; Sadato et al., Nature 1996;380:526-528; Sadato et al., Brain 1998;121:1213-1229]. Because learning Braille requires extensive training, we had sighted and blind people read raised block capital letters to determine whether all groups engage visual cortex similarly when reading by touch. Letters were passively rubbed across the right index finger at 30 mm/s using an MR-compatible drum stimulator. Age-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 84 publications
7
91
0
1
Order By: Relevance
“…Previous studies have reported somatosensory responses in human STS (Burton et al, 2006;Disbrow et al, 2001;Golaszewski et al, 2002). The present results are the first to show that these responses are co-localized with auditory and visual responses.…”
Section: Tactile Responses In Stsmssupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have reported somatosensory responses in human STS (Burton et al, 2006;Disbrow et al, 2001;Golaszewski et al, 2002). The present results are the first to show that these responses are co-localized with auditory and visual responses.…”
Section: Tactile Responses In Stsmssupporting
confidence: 75%
“…Previous human fMRI studies examining responses to somatosensory, auditory and visual stimulation have found regions responsive to all three modalities in parietal and frontal cortex, but not in the STS (Bremmer et al, 2001;Downar et al, 2000). Some studies of somatosensory processing have reported activity in STS (Burton et al, 2006;Disbrow et al, 2001;Golaszewski et al, 2002) but it is unclear if somatosensory, auditory and visual responses occur in human STSms as they do in macaque STP.…”
Section: Introductionmentioning
confidence: 99%
“…This happens in blindfolded sighted participants (Merabet et al, 2007(Merabet et al, , 2008 and blind participants (Sadato et al, 1996(Sadato et al, , 1998(Sadato et al, , 2002(Sadato et al, , 2004Cohen et al, 1999;Burton et al, 2002Burton et al, , 2006Ptito et al, 2005;Stilla et al, 2008). Several lines of evidence suggest a functional role for cross-modal plasticity: a congenitally blind Braille reader developed alexia for Braille after suffering a bilateral occipital stroke , occipital transcranial magnetic stimulation (TMS) impairs blind participants' tactile performance (Cohen et al, 1997(Cohen et al, , 1999Kupers et al, 2007), and occipital TMS elicits sensations on the fingers in some participants (Ptito et al, 2008).…”
Section: Possible Neural Mechanismsmentioning
confidence: 99%
“…We discuss our findings with respect to two possible neural mechanisms: experience-driven enlargement of somatosensory cortical representations (Pascual-Leone and Torres, 1993;Sterr et al, 1998 and recruitment of occipital cortical areas for tactile tasks (Sadato et al, 1996(Sadato et al, , 1998(Sadato et al, , 2002(Sadato et al, , 2004Cohen et al, 1999;Burton et al, 2002Burton et al, , 2006Ptito et al, 2005;Stilla et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Braille literate blind people also exhibit visual cortical activity during a variety of non-Braille tactile [6,7,16] and auditory tasks [2,5,21], which raises the question of whether Braille literacy influences visual cortex cross-modal plasticity. However, sensory deprivation alone may be sufficient to induce visual cortex reorganization because short-term visual deprivation in sighted people made visual cortex more excitable [3] and responsive during discrimination of Braille letters or auditory pitch [12].…”
Section: Introductionmentioning
confidence: 99%